The International Law of the Sea - Tanaka, Yoshifumi (Cambridge University Press, 2023)
"This book provides comprehensive and up-to-date coverage of essential issues of the international law of the sea in a systematic manner. It covers contemporary issues, such as protection of the marine biological diversity, marine plastic pollution, the Arctic, and impacts of climate change on the oceans. The book presents two paradigms of the law of the sea: the law of divided oceans and the law of our common ocean"--